A revision of the Australian humicolous and hygropetric water beetle genus Tympanogaster Perkins, and comparative morphology of the Meropathina (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2006)
The Australian endemic humicolous and hygropetric water beetle genus Tympanogaster Perkins, 1979, is revised, based on the study of 7,280 specimens. The genus is redescribed, and redescriptions are provided for T. cornuta (Janssens), T. costata (Deane), T. deanei Perkins, T. macrognatha (Lea), T. novicia (Blackburn), T. obcordata (Deane), T. schizolabra (Deane), and T. subcostata (Deane). Lectotypes are designated for Ochthebius labratus Deane, 1933, and Ochthebius macrognathus Lea, 1926. Ochthebius labratus Deane, 1933, is synonymized with Ochthebius novicius Blackburn, 1896. Three new subgenera are described: Hygrotympanogaster new subgenus (type species Tympanogaster (Hygrotympanogaster) maureenae new species; Topotympanogaster new subgenus (type species Tympanogaster (Topotympanogaster) crista new species; and Plesiotympanogaster new genus (type species Tympanogaster (Plesiotympanogaster) thayerae new species. Seventy-six new species are described, and keys to the subgenera, species groups, and species are given. High resolution digital images of all primary types are presented (online version in color), and geographic distributions are mapped. Male genitalia, representative spermathecae and representative mouthparts are illustrated. Scanning electron micrographs of external morphological characters of adults and larvae are presented. Selected morphological features of the other members of the subtribe Meropathina, Meropathus Enderlein and Tympallopatrum Perkins, are illustrated and compared with those of Tympanogaster. Species of Tympanogaster are typically found in the relict rainforest patches in eastern Australia. Most species have very limited distributions, and relict rainforest patches often have more than one endemic species. The only species currently known from the arid center of Australia, T. novicia, has the widest distribution pattern, ranging into eastern rainforest patches. There is a fairly close correspondence between subgenera and microhabitat preferences. Members of Tympanogaster (s. str.) live in the splash zone, usually on stream boulders, or on bedrock stream margins. The majority of T. (Hygrotympanogaster) species live in the hygropetric zone at the margins of waterfalls, or on steep rockfaces where water is continually trickling; a few rare species have been collected from moss in Nothofagus rainforests. Species of T. (Plesiotympanogaster) have been found in both hygropetric microhabitats and in streamside moss. The exact microhabitats of T. (Topotympanogaster) are unknown, but the morphology of most species suggests non-aquatic habits; most specimens have been collected in humicolous microhabitats, by sifting rainforest debris, or were taken in flight intercept traps. Larvae of hygropetric species are often collected with adults. These larvae have tube-like, dorsally positioned, mesothoracic spiracles that allow the larvae to breathe while under a thin film of water. The key morphological differences between larvae of Tympanogaster (s. str.) and those of Tympanogaster (Hygrotympanogaster) are illustrated. New species of Tympanogaster are: T. (s. str.) aldinga (New South Wales, Dorrigo National Park, Rosewood Creek), T. (s. str.) amaroo (New South Wales, Back Creek, downstream of Moffatt Falls), T. (s. str.) ambigua (Queensland, Cairns), T. (Hygrotympanogaster) arcuata (New South Wales, Kara Creek, 13 km NEbyE of Jindabyne), T. (Hygrotympanogaster) atroargenta (Victoria, Possum Hollow falls, West branch Tarwin River, 5.6 km SSW Allambee), T. (Hygrotympanogaster) barronensis (Queensland, Barron Falls, Kuranda), T. (s. str.) bluensis (New South Wales, Blue Mountains), T. (Hygrotympanogaster) bondi (New South Wales, Bondi Heights), T. (Hygrotympanogaster) bryosa (New South Wales, New England National Park), T. (Hygrotympanogaster) buffalo (Victoria, Mount Buffalo National Park), T. (Hygrotympanogaster) canobolas (New South Wales, Mount Canobolas Park), T. (s. str.) cardwellensis (Queensland, Cardwell Range, Goddard Creek), T. (Hygrotympanogaster) cascadensis (New South Wales, Cascades Campsite, on Tuross River), T. (Hygrotympanogaster) clandestina (Victoria, Grampians National Park, Golton Gorge, 7.0 km W Dadswells Bridge), T. (Hygrotympanogaster) clypeata (Victoria, Grampians National Park, Golton Gorge, 7.0 km W Dadswells Bridge), T. (s. str.) cooloogatta (New South Wales, New England National Park, Five Day Creek), T. (Hygrotympanogaster) coopacambra (Victoria, Beehive Falls, 2 km E of Cann Valley Highway on ’WB Line’), T. (Topotympanogaster) crista (Queensland, Mount Cleveland summit), T. (Hygrotympanogaster) cudgee (New South Wales, New England National Park, 0.8 km S of Pk. Gate), T. (s. str.) cunninghamensis (Queensland, Main Range National Park, Cunningham’s Gap, Gap Creek), T. (s. str.) darlingtoni (New South Wales, Barrington Tops), T. (Hygrotympanogaster) decepta (Victoria, Mount Buffalo National Park), T. (s. str.) dingabledinga (New South Wales, Dorrigo National Park, Rosewood Creek, upstream from Coachwood Falls), T. (s. str.) dorrigoensis (New South Wales, Dorrigo National Park, Rosewood Creek, upstream from Coachwood Falls), T. (Topotympanogaster) dorsa (Queensland, Windin Falls, NW Mount Bartle-Frere), T. (Hygrotympanogaster) duobifida (Victoria, 0.25 km E Binns, Hill Junction, adjacent to Jeeralang West Road, 4.0 km S Jeerelang), T. (s. str.) eungella (Queensland, Finch Hatton Gorge), T. (Topotympanogaster) finniganensis (Queensland, Mount Finnigan summit), T. (s. str.) foveova (New South Wales, Border Ranges National Park, Brindle Creek), T. (Hygrotympanogaster) grampians (Victoria, Grampians National Park, Epacris Falls, 2.5 km WNW Halls Gap), T. (Hygrotympanogaster) gushi (New South Wales, Mount Canobolas Park), T. (s. str.) hypipamee (Queensland, Mount Hypipamee National Park, Barron River headwaters below Dinner Falls), T. (s. str.) illawarra (New South Wales, Macquarie Rivulet Falls, near Wollongong), T. (Topotympanogaster) intricata (Queensland, Mossman Bluff Track, 5–10 km W Mossman), T. (s. str.) jaechi (Queensland, Running Creek, along road between Mount Chinghee National Park and Border Ranges National Park), T. (Topotympanogaster) juga (Queensland, Mount Lewis summit), T. kuranda (Queensland, Barron Falls, Kuranda), T. (s. str.) lamingtonensis (Queensland, Lamington National Park, Lightening Creek), T. (s. str.) magarra (New South Wales, Border Ranges National Park, Brindle Creek), T. (Hygrotympanogaster) maureenae (New South Wales, Back Creek, Moffatt Falls, ca. 5 km W New England National Park boundary), T. (Hygrotympanogaster) megamorpha (Victoria, Possum Hollow falls, W br. Tarwin River, 5.6 km SSW Allambee), T. (Hygrotympanogaster) merrijig (Victoria, Merrijig), T. (s. str.) millaamillaa (Queensland, Millaa Millaa), T. modulatrix (Victoria, Talbot Creek at Thomson Valley Road, 4.25 km WSW Beardmore), T. (Topotympanogaster) monteithi (Queensland, Mount Bartle Frere), T. moondarra (New South Wales, Border Ranges National Park, Brindle Creek), T. (s. str.) mysteriosa (Queensland), T. (Hygrotympanogaster) nargun (Victoria, Deadcock Den, on Den of Nargun Creek, Mitchell River National Park), T. (Hygrotympanogaster) newtoni (Victoria, Mount Buffalo National Park), T. (s. str.) ovipennis (New South Wales, Dorrigo National Park, Rosewood Creek, upstream from Coachwood Falls), T. (s. str.) pagetae (New South Wales, Back Creek, downstream of Moffatt Falls), T. (Topotympanogaster) parallela (Queensland, Mossman Bluff Track, 5–10 km W Mossman), T. (s. str.) perpendicula (Queensland, Mossman Bluff Track, 5–10 km W Mossman), T. plana (Queensland, Cape Tribulation), T. (Hygrotympanogaster) porchi (Victoria, Tarra-Bulga National Park, Tarra Valley Road, 1.5 km SE Tarra Falls), T. (s. str.) precariosa (New South Wales, Leycester Creek, 4 km. S of Border Ranges National Park), T. (s. str.) protecta (New South Wales, Leycester Creek, 4 km. S of Border Ranges National Park), T. (Hygrotympanogaster) punctata (Victoria, Mount Buffalo National Park, Eurobin Creek), T. (s. str.) ravenshoensis (Queensland, Ravenshoe State Forest, Charmillan Creek, 12 km SE Ravenshoe), T. (s. str.) robinae (New South Wales, Back Creek, downstream of Moffatt Falls), T. (s. str.) serrata (Queensland, Natural Bridge National Park, Cave Creek), T. (Hygrotympanogaster) spicerensis (Queensland, Spicer’s Peak summit), T. (Hygrotympanogaster) storeyi (Queensland, Windsor Tableland), T. (Topotympanogaster) summa (Queensland, Mount Elliott summit), T. (Hygrotympanogaster) tabula (New South Wales, Mount Canobolas Park), T. (Hygrotympanogaster) tallawarra (New South Wales, Dorrigo National Park, Rosewood Creek, Cedar Falls), T. (s. str.) tenax (New South Wales, Salisbury), T. (Plesiotympanogaster) thayerae (Tasmania, Liffey Forest Reserve at Liffey River), T. (s. str.) tora (Queensland, Palmerston National Park), T. trilineata (New South Wales, Sydney), T. (Hygrotympanogaster) truncata (Queensland, Tambourine Mountain), T. (s. str.) volata (Queensland, Palmerston National Park, Learmouth Creek, ca. 14 km SE Millaa Millaa), T. (Hygrotympanogaster) wahroonga (New South Wales, Wahroonga), T. (s. str.) wattsi (New South Wales, Blicks River near Dundurrabin), T. (s. str.) weiri (New South Wales, Allyn River, Chichester State Forest), T. (s. str.) wooloomgabba (New South Wales, New England National Park, Five Day Creek).